Nutritional quality and palatability of pet food from poultry by-product meal - KARTHIKEYAN, N; SINGH, R P; JOHRI, T S; TANWAR, V K (The Indian Journal of Animal Sciences, 2014)
With a view to explore the alternative use of poultry by-products as nutritious pet food, studies were conducted to formulate 3 different foods containing 15% poultry by-products, meal in combination with leaker eggs. bakery waste. cereal and cereal by-products, edible oiL permitted food additives, vitamin and mineral mixtures. The dough prepared by mixing these ingredients with water (1:1 w/v) was moulded into rectangular biscuits of about 1.5 em thickness and ovendried to moisture below 5%. The finished pet foods had high pepsin digestibility (69.7-71.4%) and were a good source of crude protein (22.9-23.7%), calcium (0.74-0.77%), phosphorus (0.67-0.70%), available lysine (0.80.0.82%). methionine (0.47-0.51 %) and ME (4.17-4.24 kcal/kg). Feeding 100g of these foods to adult pet dogs (10kg) could meet 50 to 65% of their daily maintenance requirements for ME, CP, Ca, P, available lysine and methionine as prescribed by AAFCO ( 1993). The product was highly acceptable, when fed to pet dogs. The cost of ingredients utilized for pet food preparation worked out to about Rs 15/kg.